2019
DOI: 10.3390/ijms20164005
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering GRINA/Lifeguard1: Nuclear Location, Ca2+ Homeostasis and Vesicle Transport

Abstract: The Glutamate Receptor Ionotropic NMDA-Associated Protein 1 (GRINA) belongs to the Lifeguard family and is involved in calcium homeostasis, which governs key processes, such as cell survival or the release of neurotransmitters. GRINA is mainly associated with membranes of the endoplasmic reticulum, Golgi, endosome, and the cell surface, but its presence in the nucleus has not been explained yet. Here we dissect, with the help of different software tools, the potential roles of GRINA in the cell and how they ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 174 publications
1
13
0
Order By: Relevance
“…Reactome pathway analysis showed that insulin receptor recycling, transferrin endocytosis and recycling, attachment of GPI anchor to uPAR, and post-translational modification and synthesis of GPI-anchored proteins were the major pathways associated with the positively co-expressed genes. Cell surface dynamics and post-transcriptional modification of GRINA have also been previously reported [41,53,54]. Noticeably, GO terms and pathways related to genes negatively co-expressed with GRINA were completely different from those related to positively co-expressed genes.…”
Section: Discussionsupporting
confidence: 61%
“…Reactome pathway analysis showed that insulin receptor recycling, transferrin endocytosis and recycling, attachment of GPI anchor to uPAR, and post-translational modification and synthesis of GPI-anchored proteins were the major pathways associated with the positively co-expressed genes. Cell surface dynamics and post-transcriptional modification of GRINA have also been previously reported [41,53,54]. Noticeably, GO terms and pathways related to genes negatively co-expressed with GRINA were completely different from those related to positively co-expressed genes.…”
Section: Discussionsupporting
confidence: 61%
“…Encouraged by the cross reactivity between gluten epitopes and human brain antigens, a Blast search was conducted to identify significant peptides’ sequences identity/similarity between both components. The Glutamate Receptor Ionotropic NMDA-Associated Protein 1 (GRINA) belongs to the Lifeguard family and is involved in calcium homeostasis [ 89 ]. This Protein Lifeguard 1, (UniProt: Q7Z429) was identified to have high sequence homology with Gliadin epitopes at identity level of 85.7% ( Table 3 ).…”
Section: Sequence Homology Between Gluten and Brain Tissue Componentsmentioning
confidence: 99%
“…In order to understand the characterization of GRINA domains, we analyzed the NCBI’s Conserved Domains Database (CDD) [ 13 ]. GRINA displayed two major domains: a Pro-rich domain (fragment 39-139) within an N- terminal tail and an LFG-like domain (fragment 151-367), belonging to the BI-1-like superfamily, across the transmembrane region [ 14 ].…”
Section: Domains and Expression Of Grinamentioning
confidence: 99%
“…This biochemical mechanism would be relevant in the extraintestinal manifestations of SCZ [ 33 ]. Indeed, about one-third of people with SCZ have elevated IgG antibodies to gliadin (AGA IgG) [ 14 ]. Supporting this association, a recent study with 80 healthy controls and 160 patients with SCZ showed that GRINA IgG was higher in SCZ patients than in healthy controls, and that the presence of anti-GRINA antibodies was associated with anti-AGA antibodies [ 8 ].…”
Section: Domains and Expression Of Grinamentioning
confidence: 99%
See 1 more Smart Citation